Surface functional polymers by post-polymerization modification using diarylcarbenes: introduction, release and regeneration of hydrogen peroxide and bactericidal activity. - Griffiths, J; Maliha, B; Moloney, M; Thompson, A; Hussain, I (2010)
Functionalized diarylcarbenes are excellent reactive intermediates suitable for the direct surface modification of organic polymers, and these may be used to introduce urea and thiourea functions onto polystyrene at loading levels of up to 2.3 x 10(13) molecules/cm(2). These functions are capable of the reversible binding and release of peroxide at loading levels of up to 0.6 mmol/g and give polymers that display biocidal activity against a spectrum of gram-positive and gram-negative bacteria.